BOOK REVIEW OF THE PIGMAN’S LEGACY BY PAUL ZINDEL - REZA, GALANG (LANTERN (Journal on English Language, Culture and Literature), 2015)
Beside friendship, love is also unique as it can occur unexpectedly. Love can happen to a couple in a short time or after a long period of time. The Pigman's Legacy is a book that tells us about a unique friendship and love.            It tells us about two high school students named Jon Conlon and Loraine Jensen and their relationship with a stranger named Parker Glenville, who illegally stays in their best friend’s house, Mr. Pignati. Glenville is sick old man who is running from a tax collector because he cannot pay the tax of the property he has.